The interaction of recirculation gyres and a deep boundary current - Le Bras, Isabela A.; Jayne, Steven R.; Toole, John M. (Journal of Physical Oceanography, 2018)
Author Posting. © American Meteorological Society, 2018. This article is posted here by permission of American Meteorological Society for personal use, not for redistribution. The definitive version was published in Journal of Physical Oceanography 48 (2018): 573-590, doi:10.1175/JPO-D-17-0206.1. Motivated by the proximity of the Northern Recirculation Gyre and the deep western boundary current in the North Atlantic, an idealized model is used to investigate how recirculation gyres and a deep flow along a topographic slope interact. In this two-layer quasigeostrophic model, an unstable jet imposed in the upper layer generates barotropic recirculation gyres. These are maintained by an eddy-mean balance of potential vorticity (PV) in steady state. The authors show that the topographic slope can constrain the northern recirculation gyre meridionally and that the gyre’s adjustment to the slope leads to increased eddy PV fluxes at the base of the slope. When a deep current is present along the topographic slope in the lower layer, these eddy PV fluxes stir the deep current and recirculation gyre waters. Increased proximity to the slope dampens the eddy growth rate within the unstable jet, altering the geometry of recirculation gyre forcing and leading to a decrease in overall eddy PV fluxes. These mechanisms may shape the circulation in the western North Atlantic, with potential feedbacks on the climate system. We gratefully acknowledge an AMS graduate fellowship (IALB) and U.S. National Science Foundation Grants OCE-1332667 and 1332834 (IALB and JMT). 2018-09-06